Khoáng vật phụ và sa khoáng liên quan với đá Magma Mafic - siêu Mafic ở Việt Nam - Thanh, Đỗ Thị Vân; Dương, Nguyễn Thùy; Lan, Nguyễn Thanh; Vinh, Đặng Thị (Vietnam Journal of Earth Sciences, 2018)
Subsidiary minerals and place minerals related to mafic - ultramafic rocks in Vietnam